Phytochemical and Pharmacological Effect of Phoenix dactylifera L. (Ajwa date) Seeds on Imiquimod-Induced Psoriasis Like Inflammation in Mice - Zainab Yaseen Mohammed Hasan; Mohammed Fareed Hameed; Raghad Aljazairi (Iraqi Journal of Pharmaceutical Sciences)
Abstract